2015
DOI: 10.1016/j.triboint.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface texture in reciprocating contacts – An experimental study

Abstract: The effect of surface texture on friction has been investigated experimentally for a convergentdivergent bearing, operating under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
123
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 30 publications
12
123
0
2
Order By: Relevance
“…After measuring film thickness in the reciprocating contact using a capacitance technique, they concluded that the addition of certain patterns can increase film thickness at given loads. A further notable observation, in agreement with experimental measurements, reported by the current authors [9] and Petterson and Jacobson [20], was that pockets parallel to the direction of sliding result in higher friction and lower film thickness.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…After measuring film thickness in the reciprocating contact using a capacitance technique, they concluded that the addition of certain patterns can increase film thickness at given loads. A further notable observation, in agreement with experimental measurements, reported by the current authors [9] and Petterson and Jacobson [20], was that pockets parallel to the direction of sliding result in higher friction and lower film thickness.…”
Section: Introductionsupporting
confidence: 92%
“…The experimental rig, described in detail in [9], uses a low-capacity isometric load cell to measure the friction force between a flat fused silica plate, representing the cylinder liner, and a 2-mm-wide convex AISI52100 steel pad, representing the piston ring. The 10-mm-long steel pad is curved in the direction of sliding to ensure a convergent-divergent bearing geometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dellis and Arcoumanis [27] have studied the different bubble shapes formed in the lubricant film of a piston ring assembly also using photographic methods. More recently, Vladescu et al [28] have used a laser-induced fluorescence to qualitatively visualise cavitation phenomena in surface-textured sliding bearings.…”
mentioning
confidence: 99%